PENGAKUAN DAN PENGUKURAN TRANSAKSI WAKAF PRODUKTIF PADA LEMBAGA WAKAF (STUDI KASUS: YAYASAN BAITUR RAHMAH SEJAHTERA SIDOARJO) - Arinda Dewi Nur Aini; Noven Suprayogi (Jurnal Ekonomi Syariah Teori dan Terapan, 2019)
This research aims to analyze the recognition and measurement concepts on productive waqf transaction in Baitur Rahmah Sejahtera Foundation Sidoarjo. Baitur Rahmah Sejahtera Foundation is an institution which the main activity are collecting, organizing, and distributing infaq, shadaqah and waqf. This research uses qualitative method with case study using observation, interview and documentation by collecting financial report from the treasury. The result of this research shows that waqf collection transaction is recognized as the acceptance of cash waqf and is measured based on the cash value received from the wakif. The collection of land-benefit waqf is not recognized and clearly measured, making it difficult to identify the magnitude and value of the land to which the benefits are derived. The distribution of waqf to GO Fish and Chicken Resto business is acknowledged as distribution productive waqf. The results of the management of productive endowments submitted to mauquf 'alaih are recognized as channeling of productive waqf and measured at the value of cash handed over.Keywords: Productive Waqf, Recognition, Measurement, Land-Benefit Waqf, Cash WaqfREFFERENCESAbdullah bin Muhammad ath-Thayyar et al. 2006. Ensiklopedia Fiqh Muamalah dalam Pandangan 4 Mazhab. Yogyakarta: Maktabah al Hanif.Abu Abdullah Muhammad ibn Yazid al-Qazuwaini wa Majah. Sunan Ibn Maja|h.. Kairo: Mawqi’ Wizarah al-Auqaf al-Mishriyah.Abu Zuhrah, M. 1972. Muhadarat fi al-Waqf. Cairo: Dar al Fikr al-‘Arabi.Al-Asqalāni, Ahmad bin Ali bin Hajar. 1960. Fathu al-Bāri bi SyarhShahīh al-Imām Abi ‘Abdillah Muhammad bin Ismail al-Bukhāri. Juz 6. AlQāhirah: Dār al-Kutub al-Salafiyyah.Al-Hujaili, Abdullah bin Muhammad bin Sa’d. 1999. Al-Auqāf al-Nabawiyyah wa Waqfiyāt ba’dhi al-Shahābah al-Kirām: Dirāsah Fiqhiyyah, Tārīkhiyyah, waTstāiqiyyah. Nadwah al-Maktabah al-Waqfiyyah fi alMamlakah al-‘Arabiyyah al-Su’udiyyah, 25-27 Muharram 1420. Saudi Arabia: Wazāratu al-AuqāfwaSyu’un al-Islamiyyahwa al-Auqāfwa alDa’wahwa al-Irsyād.Al-Jaziri, Abdurrahman. 1970. Kitab Fiqh Ala Mazahib al-Arba’ah. Mesir: Rihayatul Kubra.Al-Mālik, IbnuBathal Abu al-Hasan Ali bin Khalaf bin ‘Abdu. 2003. SyarhShahīh al-Bukhāri li IbniBathal. Juz 6, Cet. 2. Saudi Arabia: Maktabah al-Rusyd.Al-Qasthalani, Ahmad bin Muhammad bin Abi Bakar bin ‘Abdu al-Malik. 1905. Irsyad al-Syāri li al-SyarhShahīh al-Bukhāri. Juz 9, Cet. 7. Mesir: Al-Mathba’ah al-Kubro al-Amiriyah.Al-Syarkhasi, Syamsu al-Din Abu Bakar Muhammad bin Abi Sahl. 2000. AlMabsuth. Juz 12, Cet. 1. Beirut: Dar al-Ma’rifah.Al-Zuhaily, Wahbah. 1985. Al-Fiqh al-Islami wa Adillatuhu. Juz 8. Damaskus: Dar al-Fikr.Azhary, M. Thahir. 2003. Bunga Rampai Hukum Islam Cet. 2. Jakarta: In Hill Co.Azzam, Abdul Aziz Muhammad. 2010. Fiqh Muamalah Sistem Transaksi dalam Fiqh Islam. Jakarta: Amzah.Badan Wakaf Indonesia. 2016. Pedoman Akuntansi Wakaf. Jakarta: Departemen AgamaBank Indonesia. 2016. Wakaf: Pengaturan dan Tata Kelola yang Efektif. Jakarta: Departemen Ekonomi dan Keuangan Syariah-Bank Indonesia.Belkaoui, Ahmed Riahl. 2012. Accounting Theory, Fifth Edition. Hampshire: Cengage LearningChowdhury, Md. Shaheedur Rahaman, MohdFahmi bin Ghazali, MohdFaisol Ibrahim. 2011. Economics of Cash WAQF management in Malaysia: A proposed Cash WAQF model for practitioners and future researchers. African Journal of Business Management Vol. 5(30), hlm. 12155-12163, 30 November, 2011Dewan Syariah Nasional MUI. 2014. Himpunan Fatwa Keuangan Syariah. Jakarta: Penerbit ErlanggaDjunaidi, Achmad dan Thobieb Al-Asyhar. 2007. Menuju Era Wakaf Produktif. Depok: Mumtaz Publishing.Ghozali, Imam dan Anis Chairi. 2007. Teori Akuntansi Edisi 3. Semarang: Badan Penerbit Universitas Diponegoro.Godfrey, dkk. 2010. Accounting Theory 7th Edition. New York: John Wiley & Sons.Fanani, Muhyar. 2011. Pengelolaan Wakaf Uang. Vol 9 No 1.Hamdan, Norman, et al. 2013. Accounting for Waqf Institutions: A Review on the Adaptation of Fund Accounting in Developing the Sharia-Compliant Financial Reports for Mosque. [Paper] Presented at World Universities’ Islamic Philanthropy Conference 2013 (WIPCON 2013).Huda, N., &Heykal, M. 2010. Lembaga Keuangan Islam. Jakarta: Prenada Media Group.Ihsan, Hidayatul, et al. Towards The Better Management and Transparency of Waqf Institutions: Lessons from the Charity Commission, UK.Kahf, Monzer. 2000. Al- Waqf Al Islamy: Tatawwuruh, Idaratuh, Tanmiyyatuh. Dasmakus: Dar Al-FikrMardani. 2015. Aspek Hukum Lembaga Keuangan Syariah di Indonesia. Jakarta: Kencana. Muljono, Djoko. 2015. Buku Pintar Akuntansi Perbankan dan Lembaga Keuangan Syariah. Yogyakarta: Penerbit Andi.N. Campbell. 19.38. “Symposium: measurement and its importance for philosophy,”, Proceedings of the Aristotelian societyNasution, Hasan Mansur. 2010. Wakaf dan Pemberdayaan Umat. Jakarta: Sinar Grafika.Pusat Pengkajian Hukum Islam dan Masyarakat Madani. 2009. Kompilasi Hukum Ekonomi Syariah.  Qāsim, Hamzah Muhammad. 1990. Manār al-QāriSyarhMukhtasharShahīh al-Bukhāri. Juz 4. Damaskus: MaktabahDār al-Bayān.Republik Indonesia. Undang-Undang Nomor 41 Tahun 2004 Tentang Wakaf. (2015). Jakarta: Diperbanyak oleh Direktorat Pemberdayaan Wakaf.________________.Peraturan Pemerintah Republik Indonesia 42 Tahun 2006 Tentang Pelaksanaan Undang-Undang No. 41 Tahun 2004 Tentang Wakaf. 2015.________________.Peraturan Badan Wakaf Indonesia Nomor 4 Tahun 2010 tentang Pedoman Pengelolaan dan Pengembangan Harta Benda Wakaf. 2010. Jakarta: Badan Wakaf Indonesia.. Peraturan Menteri Agama Nomor 4 Tahun 2009 tentang Administrasi Pendaftaran Wakaf Uang. 2009. Jakarta: Menteri AgamaRahman, A. A. 2009. Peranan Wakaf dalam Pembangunan Ekonomi Umat Islam dan Aplikasinya di Malaysia. Sharia Journal , Vol 17 No. 1 113-152.Rozalinda. 2016. Fikih Ekonomi Syariah: Prinsip dan Implementasinya pada Sektor Keuangan Syariah. Jakarta: Raja Grafindo Persada.Rudianto. 2012. Pengantar Akuntansi: Konsepdan Teknik Penyusunan Laporan Keuangan. Jakarta: Penerbit ErlanggaSabiq, Sayid. 1980. Fiqh as-Sunnah. Libanon: Dar al-FikrSakina, Sri Wahyu dan Latifa Bibi Musafar Hameed. 2014. Conceptual Paper on Qualitative Characteristics: Waqf Accounting in Malaysia. International Conference of Postgraduate Research 2014Sari, Elsi Kartika. 2007. Pengantar Hukum Zakat dan Wakaf. Jakarta: GrasindoShihab, M. Quraish. 2002. Tafsir Al-Mishbah. Jakarta: Lentera HatiSoetedjo, Soegeng. 2009. Pembahasan Pokok-Pokok Pikiran Teori Akuntansi Vernon Kam. Surabaya: Airlangga University PressSulaiman, Maliah, Mohd Akhyar Adnan dan Putri Nor Suad Megat Mohd Nur. 2014. Trust Me! A Case Study of the International Islamic University Malaysia’s Waqf Fund. Review of Islamic Economics, vol. 13, no. 1, 2009, hlm. 69–88.SS Stevens, 1951. Handbook of experimental psychology. New York: John Wiley.Triyuwono, Iwan. 2006. Akuntansi Syariah: Perspektif, Metodologi, danTeori. Jakarta: Raja GrafindoPersada.Tuanakotta, Theodorus M. 1984. Teori Akuntansi. Jakarta: Lembaga Penerbit Fakultas Ekonomi Universitas Indonesia.Yaacob, Hisham, dkk. 2015. Accountability Through Accounting and Reporting Lenses. Humanomics, Vol. 31 Iss. 3 hlm. 299-313.Yin, Robert K. 2014. Case Study Research: Design and Methods Fifth Edition. California: SAGE_____________.2016. Qualitative Research From Start to Finish, Second Edition. New York: The Guilford Press.